Persepsi Label Halal dan Pemasaran Digital "Nglarisi" dalam Meningkatkan Penjualan pada UMK Gandeng-Gendong Yogyakarta - Mariam, Siti; Fajriati, Imelda (LABATILA : Jurnal Ilmu Ekonomi Islam, 2024)
This research aims to analyze and explore the perceptions of Micro and Small Enterprises (UMK) regarding the effectiveness of the halal label factor and "Nglarisi" digital marketing in increasing sales. This research is conclusive research with a qualitative approach, which is based on phenomena in the field. Data was collected through interviews and documentation of MSE actors who are members of the Gandeng-Gendong group. Gandeng-Gendong itself is one of the Yogyakarta City government programs which was formed to reduce and alleviate poverty, as well as to improve community welfare. The research results show that the halal label factor is seen as not being effective in increasing sales for the MSEs in the Gandeng-Gendong group. The majority of buyers do not question whether there is a halal label on the packaging, but it is the attitude of trust towards the seller that is more deeply rooted in the minds of buyers. The digital marketing factor through the "Nglarisi" application is seen as positive by business actors. That means the digital marketing through the "Nglarisi" application is quite effective in increasing sales.